Channa brunnea, a new species of snakehead (Teleostei: Channidae) from West Bengal, India - Praveenraj, Jayasimhan; Uma, Arumugam; Moulitharan, Nallathambi; Kannan, Rajesh (Zootaxa, 2019)
Channa brunnea, a new species of snakehead fish lacking pelvic fins, from West Bengal, India, is distinguished from its pelvic fin-less congeners by possessing an uniform dark brown body, ochre to bright-orange blotches on the caudal fin, fewer dorsal and anal-fin rays (35–37 vs. 47–51 and 24 vs. 28–32, respectively), fewer vertebrae (43 vs. 45–57), and fewer lateral-line scales (43–46 vs. 51–63). Though Channa brunnea superficially resembles C. bleheri, it can be distinguished from the latter by possessing dark-brown oblique markings on the upper half of the body; transverse scale rows (4½–5½ vs. 3½); pre-anal scales (22–26 vs. 17–20); 2 rows of teeth in the fifth ceratobranchial, the outer row with 16 large conical teeth (vs. 3 rows of teeth, the outer row with 13 large conical teeth); dentary with 20 large, stout, conical teeth in the inner row (vs. 32 medium-sized conical teeth); and a Kimura’s two parameter (K2P) distance of 9.8–10.6%.